Interpreting qualitative data : methods for analyzing talk, text, and interaction - Silverman, David (SAGE Publications, 2006)
This text offers practical and sensible advice on the central issues involved in qualitative research, from one of the leading researchers. The book assesses an unrivalled range of qualitative methods, and the strengths of methodologies